Organic Charge‐Transfer Complexes for Near‐Infrared‐Triggered Photothermal Materials. Issue 1 (16th November 2022) - An, Lei; Zheng, Liangyu; Xu, Chao; Zhao, Ziqi; Gao, Fan; Wang, Wenjun; Ou, Changjin; Dong, Xiaochen
Abstract : Organic photothermal materials excited by near‐infrared (NIR) light display promising applications in biomedicine, optoelectronic devices, water purification, and so on. However, the most NIR responsive organic photothermal materials are in the mire of laborious synthesis, high cost, and limited functions. The newly emerging charge‐transfer complexes (CTCs) are promising photothermal materials to solve the issues and are receiving much attention. Compared with traditional photothermal agents, CTCs possess strong NIR absorption, high photo‐to‐thermal conversion efficiency, simple synthesis, and function‐directed material design. Herein, the latest advances in NIR‐excited CTCs for photothermal agents are systematically summarized. First, the basic structure–performance relationships are introduced. Then, several important factors affecting the photothermal properties of the CTCs are discussed from the sight of photophysics, and a comprehensive comparison is made among the nanoparticle systems. Finally, organic photothermal CTCs are highlighted as a multifunctional platform for applications and the perspective is given. Abstract : This review mainly introduces the relationships between stacking modes and properties of charge‐transfer complexes (CTCs) with near‐infrared responsiveness, and the photophysical processes, especially the effect of group vibration, lattice relaxation, etc., on the photothermal performance are discussed. Additionally, the recent advances in organic photothermal CTCs including anticancer, antibacterial, water purification, and photothermal catalysis are summarized.